EXPERIENCE FOR SLIDING METHOD OF STEEL CONVEYOR’S GALLERY PLACEMENT (Collection of scientific works «Modern structures of metal and wood», 2019)
The  article  describes  the  experience  of  installing  a  metal  146  meter  conveyor  gallery. According  to  the  project,  the  gallery  should  be  arranged  above  the  railway  tracks,  without interrupting  the  operation  of  railway  transport  for  a  long  time.  After  analyzing  all  possible installation  variants  and  considering  the  possibilities  of  the  contractor,  a  non-trivial  method  of carrying out works on the arrangement of the conveyor gallery was chosen. For this purpose, the sliding method was used, which suppose the gallery gradually moved to the arranged supports. As it moves,  it  changes  its  design  scheme  and,  as  a  consequence,  efforts  in  the  structural  elements. Additional difficulties were added by the fact that the installation was carried out at height of more than 30 m above the level of the railway track, which imposed many restrictions when performing the installation work. To reduce the effort in the elements of the gallery when moving, there was mounted a backbone, 10 m long to its edge. In a case that the design scheme of the gallery has been changing  several  times,  a  detailed  numerical  analysis  of  the  behavior  of  the  supports  and  every elements of the gallery during the installation work by the finite elements software program "LIRA-SAPR" was performed. The calculations took into account additional  installation  loads and wind loads, the which value was taken from the data from the meteorological monitoring service. Wind speed was up to 10 m / s.  Also, using the techniques which  was performed  in the software, the dynamic  characteristics  of  the  gallery  were  evaluated.  Before  the  installation  works  there  were carried out full-scale tests of the gallery’s structures, where the deflections were measured at the maximum  length  of  the  console  when  pushed.  During  the  tests,  the  drawing  of  the  gallery  was simulated  and  various  mounting  cases  were  checked.  Numerical  calculations  and  full-scale  tests confirmed the possibility of installation work on the arrangement of the metal conveyor gallery by the chosen method, which was successfully done in 9 days.